Peningkatan Pemahaman ‘Islamic Leadership’ untuk Pemuda Sumatera Utara - Muhammad Kaulan Karima; Ramadhani Ramadhani; Toni Nasution (Jurnal Abdi Mas Adzkia, 2021)
ABSTRACT. The case for youth moral decadentism at this time is veryconcerning, plus the condition of the nation is being deteriorated economically.The morality of the younger generation is certainly very worried, because theyare the ones who will be the leaders of the nation in the future. In Islam,leadership is one of the important elements, because the enforcement of justice isimpossible to achieve except with power/authority. Therefore, this devotion aimsto realize a strong, optimistic, intelligent, and religious young Islamic leader".This type of qualitative research is descriptive. The results of this study foundthat the perception of youth about Islamic leadership is indispensable in order tooptimize the development of human resources and smarten and solve theproblems of the nation's life in achieving a bright future, because it is the nextgeneration of youth who will fight for sustainability. Leaders must leadaccording to islamic values such as having courage in problem solving,encouraging change, showing example, honesty, maturity, loyalty, enthusiasm,determination, conviction, responsibility, hard work, discipline, and wisdom. Keywords: Islamic Leadership, Young Generation, North Sumatera